Kontribusi Kecerdasan Emosional Dan Motor Ability Dengan Kemampuan Bermain Kempo - Zahara Zahara (Center for Research and Community Service (LPPM) University of Abulyatama, 2019)
The element of physical condition is one of the most important elements observed by every sportsman. This is because the physical element has a huge influence on determining the mastery of the other elements. Besides having the ideal physical and Antrhopometri, the athlete of the sport of Kempo also requires a good mental condition. One of the mental factors to note is the level of confident athletes in preparing to do the match. This relates to the form of matches that are always physically faced during the game. Athletes who have less emotional intelligence on their own will experience obstacles in achieving achievements. The population in this research is the provincial athletes in Aceh, which amounted to 26 people and all made samples in this study. The instrument used in this research is using a poll, motor ability test i.e. 1) throwing tests on target; 2) Kelentukan Togok and waist test; 3) Jump far without a prefix; 4) Complete and awake test; 5) push up test; 6) Back and forth and a Kempo play ability test. The analysis of data in this study was processed by using statistical formulas in the form of calculation of average values (mean), standard deviation (SD) and correlational test. The results of analysis of research data obtained the following conclusions, 1) there is a positive and significant relationship between emotional intelligence and the ability to play a game of development of ACEH Pengprov athletes (r = 0.41); 2) There is a positive and significant relationship between Motor Ability with the ability to play the athletes of the Pengprov Aceh PROLIFERATION (r = 0.58); 3) There is a relationship of emotional intelligence and Motor Ability with the ability to play the the athlete of the development of ACEH (R = 0.50). The results of the hypothesis testing showed that Fcount = 2.19 â‰¥ Ftabel = 1.711 then Emotional intelligence and Motor Ability had a significant connection to the ability of the Kempo play.